(untitled) (Palíndromo, 2025)
This paper addresses theoretical and plastic assumptions of the Minimal Art by confroting elements discussed in the works of Donald Judd and Robert Smithson. Considering the investigation of the remains of a given futuristic imagery manifested in the works of both artists, the following research leans over the notions of specificity, worked by Judd, and entropy, problematized by Smithson. Aiming to offer a brief contribution to the broader debate around the topic of complex temporalities in contemporary art, the approach proposed by this paper reflects on the idea of imagined and abandoned futures within some of the most prominent Minimalism artworks.